Living on the edge: Exploring the role of coastal refugia in the Alexander Archipelago of Alaska. Issue 4 (1st February 2019) - Sawyer, Yadéeh E.; MacDonald, Stephen O.; Lessa, Enrique P.; Cook, Joseph A.
Abstract: Although islands are of long‐standing interest to biologists, only a handful of studies have investigated the role of climatic history in shaping evolutionary diversification in high‐latitude archipelagos. In this study of the Alexander Archipelago (AA) of Southeast Alaska, we address the impact of glacial cycles on geographic genetic structure for three mammals co‐distributed along the North Pacific Coast. We examined variation in mitochondrial and nuclear loci for long‐tailed voles ( Microtus longicaudus ), northwestern deermice ( Peromyscus keeni ), and dusky shrews ( Sorex monticola ), and then tested hypotheses derived from Species Distribution Models, reconstructions of paleoshorelines, and island area and isolation. In all three species, we identified paleoendemic clades that likely originated in coastal refugia, a finding consistent with other paleoendemic lineages identified in the region such as ermine. Although there is spatial concordance at the regional level for endemism, finer scale spatial and temporal patterns are less clearly defined. Demographic expansion across the region for these distinctive clades is also evident and highlights the dynamic history of Late Quaternary contraction and expansion that characterizes high‐latitude species. Abstract : In this study of the Alexander Archipelago (AA) of Southeast Alaska, we address the impact of glacial cycles on geographic genetic structure for three mammals co‐distributed along the North Pacific Coast. In all three species, we identified paleoendemic clades that likely originated in coastal refugia, a finding consistent with other paleoendemic lineages identified in the region such as ermine.